Vertical Cooperative Advertising with Substitute Brands. (1st October 2013) - Chen, You-Hua; Wen, Xiao-Wei
Abstract : Cooperative (co-op) advertising is attracting more and more attention. This paper analyzes co-op advertising behavior based on a dual-brand model with a single manufacturer and a single retailer, and some interesting conclusions are achieved. Firstly, the firm in the supply chain advertises both brands, and the difference of advertising expenditure is not very large in equilibrium. Secondly, the retailer's advertising and the manufacturer's participation ratios depend on both the retailer's and the manufacturer's marginal profits. Thirdly, the stimulating effect increases the advertising investment while the competition effect decreases it, but they have no effect on the manufacturer's participation ratio. Fourthly, co-op advertising is more sensitive to the manufacturer's marginal profits than those of the retailer. Lastly, total advertising investment and profit are greater under cooperative decision than under Stackelberg decision.